IDENTIFIKASI JAMUR KONTAMINAN BERDASARKAN KEBERSIHAN KARPET TEMPAT IBADAH DI KELURAHAN TAPOS - Zuraida; Dahlia; Dzia Ulhaq Rohadatul Aisy (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Mosques and prayer rooms are frequently visited places of worship for Muslim communities. Prayer activities commonly use prayer mats or carpets that directly cover the floor and may serve as a medium for microbial contamination, particularly fungi. Open ventilation systems and frequent access from outside environments allow various airborne pollutants, including fungal spores, to enter the worship area. This study aimed to determine the presence and types of fungal contaminants on carpets in places of worship and their relation to carpet maintenance practices such as sun-drying, washing, and vacuuming. This study used a descriptive analytic method with a population and sample of 20 worship places consisting of mosques and prayer rooms in Tapos Village. Fungal examination was conducted using Sabouraud Dextrose Agar (SDA) media, and the results were analyzed descriptively using percentage analysis. The results showed that 100% of worship carpet samples were contaminated with fungi. The identified fungal species included Candida spp (70%), Monilia sitophila (50%), Penicillium spp (45%), Mycelia sterilia (40%), Aspergillus niger (30%), Aspergillus flavus (30%), Fusarium spp (30%), Rhodotorula rubra (30%), Absidia spp (20%), Aspergillus fumigatus (15%), Aspergillus versicolor (5%), and Curvularia spp (5%). Carpet maintenance practices such as sun-drying, washing, and vacuuming were found to help reduce the spread of fungal contamination in places of worship